2013
DOI: 10.1021/ac403391q
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free In-Flow Detection of Single DNA Molecules using Glass Nanopipettes

Abstract: With the view of enhancing the functionality of label-free single molecule nanopore-based detection, we have designed and developed a highly robust, mechanically stable, integrated nanopipette-microfluidic device which combines the recognized advantages of microfluidic systems and the unique properties/advantages of nanopipettes. Unlike more typical planar solid-state nanopores, which have inherent geometrical constraints, nanopipettes can be easily positioned at any point within a microfluidic channel. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 54 publications
6
62
0
Order By: Relevance
“…26,27 The reproducibility of the molecular delivery between individual pulses is illustrated in Gershow and Golovchenko, have shown that the probability of recapture decreases dramatically with the time elapsed before the application of a reverse potential (V + here). 34 Indeed, recaptured DNA molecules were not observed in the V + current time traces as show in Supporting Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 The reproducibility of the molecular delivery between individual pulses is illustrated in Gershow and Golovchenko, have shown that the probability of recapture decreases dramatically with the time elapsed before the application of a reverse potential (V + here). 34 Indeed, recaptured DNA molecules were not observed in the V + current time traces as show in Supporting Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In fact nanopipettes are predominantly used as an analytical platform for the detection of single molecules by transporting molecules from the outside reservoir to the inside of the nanopipette. 10,12,13,[24][25][26][27] . However, this does not take advantage of utilizing the nanopipette as a label-free single-molecule delivery vehicle.…”
Section: Introductionmentioning
confidence: 99%
“…Typical SICM experiments are performed in moderate 19 to high ionic strengths (>100 mM), 3,31,32,45,67,68 as are many nanopipette measurements. 14,15,18,19 Under these conditions, the diffuse double layer is expected to be compressed to a sub-nanometer scale, and therefore undetectable, level according to: 50…”
Section: Characterization Of Nanopipettes In High Ionic Strength Mediamentioning
confidence: 99%
“…14,15,18,19 Under these conditions, the diffuse double layer is expected to be compressed to a sub-nanometer scale, and therefore undetectable, level according to: 50…”
Section: Characterization Of Nanopipettes In High Ionic Strength Mediamentioning
confidence: 99%
“…They stressed several advantages of the nanopipette over the nanopore, including its mechanical strength and ease of fabrication. Another advantage-the small physical size and needle-like shape enabling precise positioning and experiments in small spaces-was utilized by Gong et al [68], who developed an integrated nanopipette-microfluidic device in which the pipette could be positioned at any point within a microfluidic channel. In this way, it was possible to detect and discriminate between DNA molecules of varying lengths travelling through the microfluidic channel.…”
Section: Resistive-pulse and Rectification Sensing Of Biomolecules Wimentioning
confidence: 99%